2016
DOI: 10.3390/md14100182
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of VEGF165-Chitosan Nanoparticles for the Treatment of Radiation-Induced Skin Injury in Rats

Abstract: Radiation-induced skin injury, which remains a serious concern in radiation therapy, is currently believed to be the result of vascular endothelial cell injury and apoptosis. Here, we established a model of acute radiation-induced skin injury and compared the effect of different vascular growth factors on skin healing by observing the changes of microcirculation and cell apoptosis. Vascular endothelial growth factor (VEGF) was more effective at inhibiting apoptosis and preventing injury progression than other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…VEGF is a mitotic stimulator and chemotactic factor specific to endothelial cells. As an important regulator of angiogenesis, VEGF can activate vascular endothelial cells, improve local vascular permeability, promote the formation of new blood vessels and play an important role in wound healing and tissue reconstruction [ 20 , 30 ]. This study found that, after exposure of HUVECs to different culture conditions, the content of TGF-β1 in the collagen-chitosan mixed solution was significantly higher than that in each single solution, and that in each single solution was significantly higher than the control.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a mitotic stimulator and chemotactic factor specific to endothelial cells. As an important regulator of angiogenesis, VEGF can activate vascular endothelial cells, improve local vascular permeability, promote the formation of new blood vessels and play an important role in wound healing and tissue reconstruction [ 20 , 30 ]. This study found that, after exposure of HUVECs to different culture conditions, the content of TGF-β1 in the collagen-chitosan mixed solution was significantly higher than that in each single solution, and that in each single solution was significantly higher than the control.…”
Section: Discussionmentioning
confidence: 99%
“…developed VEGF chitosan nanoparticles by combining chitosan nanoparticles with vascular endothelial growth factor (VEGF) to improve local microcirculation and enhance the protective effect on vascular endothelial cells and skin injury. [ 167,168 ] As more and more successful attempts to use intrinsic nanomaterials for radiation protection arise, we believe that there is still much space left for acquiring more innovations in this interesting and promising area.…”
Section: Research Status Of Intrinsic Nano‐radioprotectantsmentioning
confidence: 99%
“…IR can kill tumor cells by generating free radicals or ROS ( 157 ). Tumor cells or tumor stem cells resistant to radiotherapy often maintain low levels of ROS and have strong anti-oxidative stress effects ( 158 ).…”
Section: Hdacs and Radiotherapy Resistancementioning
confidence: 99%